Development and validation of a novel index to assess the perceived impact of sports-related oro-dental trauma among adolescents: findings from Sri Lanka - Iresha Udayamalee; Hemantha Amarasinghe; Ping Zhang; Newell Johnson (BMC, 2023)
Abstract Background Sports-related oro- dental trauma, such as tooth fracture, displacement, mobility, and avulsion, cause significant concern among adolescent players due to detrimental impacts. The current study aims to develop, validate and assess the reliability of a simple index as a questionnaire to assess the impact of sports-related oro-dental trauma both untreated and treated, among adolescent school children in Sri Lanka. Methods AODTII, an adolescent oro-dental trauma impact index, was developed and validated using a mixed-method approach. Items for the index were generated by quantitative as well as qualitative analysis of the results from Oral Health-Related Quality of Life Questionnaires, personnel interviews with experts and focus group discussions with adolescents. Principal component analysis and Exploratory factor analysis were used to create the index. The index was validated in the Sinhala language, and the reliability of the index was assessed using a separate sample in the school context in the Colombo district. Results The initial list of 28 items was reduced to 12 by the Principal Component Analysis. Exploratory Factor Analysis categorised the variables into four latent constructs; physical impact, psychosocial effect influenced by peer pressure, the impact of oral health care and the impact caused due to unmet dental trauma treatment need. The cut-off values of the AODTII were based on PCA. The index achieved the Content Validity Ratio of 88.33. The construct validity was assessed with confirmatory factor analysis by developing a structural equation model. It obtained good model fit indices of RMSEA value of 0.067, SRMR of 0.076, CFI of 0.911 and the Goodness of Fit index of 0.95. The homogeneity was ensured with convergent and discriminant validity. The Cronbach's alpha value was 0.768, ensuring reliability. The index assesses the level of impact due to oro- dental trauma and identifies whether the adolescents perceive it significantly or not. Conclusion Twelve-item AODTII emerged as a reliable and valid tool to assess the perceived impact of untreated and treated sports-related oro- dental trauma on Sri Lankan adolescents with implications for its use in other populations. Further research is required to improve the translational value of AODTII. Moreover, the tool is potential as a patient-centred communication tool, clinical adjunct, advocacy tool and a useful OHRQoL index. However, it is needed to be supported end-users' feedback.